Kompensasi Tanah Wakaf Dalam Pengadaan Tanah Untuk Tol Semarang Demak Seksi II - Khaidar Alifika El Ula; Ana Silviana (Notarius, 2023)
AbstractThe need for land has increased since the intensity of development carried out by the government has increased, this is in contrast to the availability of land owned, land acquisition is an alternative that can be carried out by the government. The status of the land that was acquired is not only ownership rights but waqf land which is intended for the benefit of the people, land acquisition for the construction of the Semarang Demak toll road section II has areas of waqf land that are affected. The objective of this research is to find out the compensation arrangements for waqf land affected by land acquisition activities for section II of the Semarang Demak toll road and how compensation for waqf land is implemented in land acquisition activities for section II of the Semarang Demak toll road. The writing of this article uses a juridical empirical research method. Compensation arrangements for waqf land use a regent's decree in accordance with the Decree of the Governor of Central Java, and for the process itself it is carried out from a team formed by the Ministry of Religion of Demak Regency.Keywords: compensation; waqf; semarang-demak toll road.AbstrakKebutuhan tanah mengalami peningkatan sejak intensitas pembangunan yang terus dilakukan pemerintah mengalami peningkatan, hal ini bertolak belakang dengan ketersediaan tanah yang dimiliki, pembebasan tanah menjadi alternatif yang dapat dilakukan oleh pemerintah. Status tanah yang dibebaskan tidak hanya kepemilikan secara hak milik akan tetapi tanah wakaf yang peruntukannya untuk kemaslahatan umat, pembebasan tanah untuk pembangunan tol Semarang Demak seksi II terdapat bidang tanah wakaf yang terkena. Penelitian ini mempunyai tujuan untuk mengetahui pengaturan kompensasi tanah wakaf yang terkena kegiatan pembebasan tanah untuk tol Semarang Demak seksi II dan bagaimana pelaksanaan kompensasi tanah wakaf dalam kegiatan pengadaan tanah untuk tol Semarang Demak seksi II. Penulisan artikel ini menggunakan metode penelitian secara yuridis empiris. Pengaturan kompensasi tanah wakaf menggunakan surat keputusan bupati sesuai dengan Surat Keputusan Gubernur Jateng, dan untuk prosesnya sendiri dilakukan dari tim bentukan Kementerian Agama Kabupaten Demak.Kata kunci: kompensasi; wakaf; tol semarang demak.